POSTCOLONIAL ARABIC FICTION REVISITED: NATURALISM AND EXISTENTIALISM IN GHASSAN KANAFANI’S MEN IN THE SUN - Neimneh, Shadi Saleh (Indonesian Journal of Applied Linguistics, 2017)
This article looks into the postcolonial Arabic narrative of Ghassan Kanafani to examine its underplayed existential and naturalistic aspects. Postcolonial texts (and their exegeses) deal with the effects of colonization/imperialism. They are expected to be political and are judged accordingly. Drawing on Kanafani’s Men in the Sun (1963), I argue that the intersection among existentialism and naturalism, on the one hand, and postcolonialism, on the other, intensifies the political relevance of the latter theory and better establishes the politically committed nature of Kanafani’s fiction of resistance. In the novella, the sun and the desert are a pivotal existential symbol juxtaposed against the despicable life led by three Palestinian refugees. The gruesome death we encounter testifies to the absurdity of life after attempts at self-definition through making choices. The gritty existence characteristic of Kanafani's work makes his representation of the lives of alienated characters more accurate and more visceral. Kanafani uses philosophical and sociological theories to augment the political nature of his protest fiction, one acting within postcolonial parameters of dispossession to object to different forms of imperialism and diaspora. Therefore, this article explores how global critical frameworks (naturalism and existentialism) enrich the localized contexts essential to any study of postcolonial literature and equally move the traditional national allegory of Kanafani to a more realist/unidealistic level of political indictment against oppression.